1988
DOI: 10.1063/1.454523
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of low energy reactive ions with surfaces. III. Scattering of 30–200 eV Ne+, O+, C+, and CO+ from Ni(111)

Abstract: Time-of-flight (TOF) and energy distributions of 30–200 eV Ne+, O+, C+, and CO+ scattered from Ni(111) have been investigated using pulsed ion beam techniques and classical trajectory simulations. The experiments probe the interaction potentials and the applicability of the binary collision approximation in the low energy range. The experimental scattering energies are in good agreement with the energies predicted by the classical treatment. Scattering of atomic projectiles at primary energies as low as 30 eV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Observations of O Ϫ have previously been explained by several authors using resonant charge-transfer mechanisms. 3,5,18,20,45,46 Quantitative predictions of resonant charge-transfer probabilities require treating the intrinsic multistate character of this problem, including that arising from the degenerate p electrons in oxygen; 18 this is beyond the scope of this paper.…”
Section: B Negative-ion Formationmentioning
confidence: 99%
“…Observations of O Ϫ have previously been explained by several authors using resonant charge-transfer mechanisms. 3,5,18,20,45,46 Quantitative predictions of resonant charge-transfer probabilities require treating the intrinsic multistate character of this problem, including that arising from the degenerate p electrons in oxygen; 18 this is beyond the scope of this paper.…”
Section: B Negative-ion Formationmentioning
confidence: 99%
“…With these they form intermediate molecular orbitals, which describe an electronically excited state of the system. As the two components separate again, diabatic crossings between the potential energies of the transient molecule lead the system into states which correlate at infinity with excited products [39][40][41][42]. Unlike AN, this reaction step does involve the motion of heavy particles and is therefore much slower than the AN step, and subsequent to it.…”
Section: Resultsmentioning
confidence: 99%
“…No sputtering was performed in order to preserve the nominal atomic composition of the sample surface. 25 Ion scattering experiments were carried out in a homebuilt TOF-SARS system similar to the one described by Rabalais et al 21 A schematic diagram of the system is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%